2016
DOI: 10.1038/srep37797
|View full text |Cite
|
Sign up to set email alerts
|

A Role of the FUZZY ONIONS LIKE Gene in Regulating Cell Death and Defense in Arabidopsis

Abstract: Programmed cell death (PCD) is critical for development and responses to environmental stimuli in many organisms. FUZZY ONIONS (FZO) proteins in yeast, flies, and mammals are known to affect mitochondrial fusion and function. Arabidopsis FZO-LIKE (FZL) was shown as a chloroplast protein that regulates chloroplast morphology and cell death. We cloned the FZL gene based on the lesion mimic phenotype conferred by an fzl mutation. Here we provide evidence to support that FZL has evolved new function different from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…The two significantly expressed heat stress transcription factors (PDACT_KE332562.1_G003770 and PDACT_KE332562.1_G003780) were putative orthologs of Arabidopsis heat stress transcription factor A-2 (HsfA2), known to regulate the expression of a number of heat shock proteins (HSPs) in Arabidopsis and to induce the expression of L-ascorbate peroxidase 2 (APX2), Inositol-3-phosphate synthase isozyme 2 (IPS2) and galactinol synthases 1 and 2 (GolS1) [ 34 ]. Additionally, two negative regulators of cell death, orthologs of Bax inhibitor-1 family protein and Fuzzy Onions Like [ 35 , 36 ], were highly expressed in all three conditions suggesting suppression of cell death, as well as one positive regulator, putative ortholog of Arabidopsis BAG6 chaperone regulator [ 37 ]. In Arabidopsis, BAG6 is a positive regulator of heat shock factors and cell death.…”
Section: Resultsmentioning
confidence: 99%
“…The two significantly expressed heat stress transcription factors (PDACT_KE332562.1_G003770 and PDACT_KE332562.1_G003780) were putative orthologs of Arabidopsis heat stress transcription factor A-2 (HsfA2), known to regulate the expression of a number of heat shock proteins (HSPs) in Arabidopsis and to induce the expression of L-ascorbate peroxidase 2 (APX2), Inositol-3-phosphate synthase isozyme 2 (IPS2) and galactinol synthases 1 and 2 (GolS1) [ 34 ]. Additionally, two negative regulators of cell death, orthologs of Bax inhibitor-1 family protein and Fuzzy Onions Like [ 35 , 36 ], were highly expressed in all three conditions suggesting suppression of cell death, as well as one positive regulator, putative ortholog of Arabidopsis BAG6 chaperone regulator [ 37 ]. In Arabidopsis, BAG6 is a positive regulator of heat shock factors and cell death.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies performed in the plant model Arabidopsis thaliana demonstrated that the absence of Fzl is responsible for a slow growth phenotype associated with pale green or partly chlorotic leaves [20,22], enlarged chloroplasts containing morphologically altered thylakoids [20] as well as activation of autophagy and cell death pathways [22,23]. In addition, photosynthetic impairment was observed in pale green leaves [21].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of Fzl induces a slow growth phenotype associated with the development of pale green leaves in the Columbia (Col-0) ecotype [20,21]. In the Landsberg erecta (L er ) background, the slow growth was conserved but the older leaves developed chlorotic areas instead of homogenous bleaching [22,23]. fzl cells display enlarged chloroplasts with morphologically altered thylakoids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations